2023
DOI: 10.1021/acs.joc.3c00402
|View full text |Cite
|
Sign up to set email alerts
|

Nickel-Catalyzed Alkylation of Oxindoles with Secondary Alcohols

Abstract: Herein, we have demonstrated a simple nickelcatalyzed C-3-selective alkylation of 2-oxindoles using a wide variety of secondary alkyl alcohols. As a special highlight, functionalization of the cholesterol derivative was reported. Control experiments, initial mechanistic studies, and deuterium-labeling experiments were performed for the alkylation process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…The late-stage functionalisation of cholesterol demonstrated the synthetic potential of the process (Scheme 11). 47…”
Section: Alkylation Reactionmentioning
confidence: 99%
“…The late-stage functionalisation of cholesterol demonstrated the synthetic potential of the process (Scheme 11). 47…”
Section: Alkylation Reactionmentioning
confidence: 99%
“…[9] Later, the research group of Morrill and coworkers reported the iron-catalyzed C-alkylation of oxindoles at 150 °C. [10] Contributions from the groups of Gnanaprakasam, [11] Piersanti, [12] Sundararaju, [13] Banerjee, [14] Mitsudome, [15] Beller, [16] Balaraman [17] and Antonino [18] have illustrated that varieties of transition metals (Ru, Ir, Co, Ni, Mn, Ag…) were able to intrigue such alkylation reactions, leading to versatile alkylated oxindoles. Nevertheless, extremely high temperature was needed for these reactions.…”
Section: Introductionmentioning
confidence: 99%